Strategi Pemasaran Digital untuk Meningkatkan Ekonomi Kreatif Melalui Pengolahan Limbah Daun Nanas: Studi Kasus pada UKM Alfiber Subang - Yuyun Yuniarsih; Silsi Sabila; M. Dadi Priadi; Witri Cahyati (Departement of Mathematics Education, 2023)
This research was conducted to determine the implementation of digital marketing strategies at the Alfiber Subang SMEs with the aim of expanding the market and increasing sales of Alfiber products produced from pineapple leaf waste processing. This study focused on the implementation of digital marketing strategies, the challenges faced, and the impact of the implementation of digital marketing strategies on the increase of creative economy in the Alfiber Subang SMEs. The aim of this research is to explore the potential of the creative economy through pineapple leaf waste processing, with a focus on effective digital marketing strategies for the Alfiber Subang SMEs.The results of this research indicate that the Alfiber Subang SME has great potential to increase the creative economy through pineapple leaf waste processing. However, there are still obstacles in marketing their products digitally. Therefore, this research proposes several effective digital marketing strategies, including the use of social media, websites, and e-commerce, as well as optimizing digital content. This research is expected to contribute to the Alfiber Subang SME and relevant parties in facing challenges and utilizing opportunities in digital marketing to increase the creative economy through pineapple leaf waste processing.